Pengaruh penambahan tepung daun Ciplukan (Physalis angulata L) yang difermentasi dengan Em4 pada pakan untuk pertumbuhan dan kelangsungan hidup ikan Nila (Oreochromis nilotius) - Rustiana Widaryati (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2019)
The purpose of this study was to determine the Effect of addition of Ciplukan (Physalis angulata L) flour fermented with EM 4 in feed to increase the growth of Nile Tilapia (Oreochromis niloticus). Treatments given A 0.5 gr / ml, B 1 gr / ml, C 1.5 gr / ml. Observation parameters were absolute growth, feed conversion and survival. The results of the study showed that giving Ciplukan flour fermented with probiotics in commercial feed had a very significant influence on absolute growth and survival of Nile Tilapia. The best dose of 1 gr / ml (treatment B) gave the highest growth of 1.7 followed by treatment A (0.5 gr / ml) of 0.8 and the lowest in treatment C (1.5 gr / ml) was 0.5. Keywords : Ciplukan (Physalis angulata L), EM 4 (Effective Microorganism 4), Nile Tilapia